AGENTS OF TRANSFORMATION: PARTHIVAPURAM SREE PARTHASARATHI TEMPLE AND ITS IMPACT ON SOCIAL STRUCTURES IN KANYAKUMARI DISTRICT. - K, Santhosh Kumar; Thanammal, K.K. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In Kanyakumari district, the Parthivapuram Sree Parthasarathi Temple has long been a centre of religious devotion, but it also plays an important role in changing societal systems. This essay investigates the centuries-long effects of the temple on social structures, customs, and group identities. The temple has served as a catalyst for social transformation from its early years as a location of royal patronage to its current function in influencing local administration. Its impact changes the social structure of the area in a number of ways, such as caste relations, gender roles, and community cohesion. Additionally, the temple is essential for socioeconomic advancement, cultural preservation, and establishing a forum for social integration that promotes harmony among various cultures. The historical background, social welfare initiatives, community involvement, and the temple's place in Kanyakumari's current political and social scene are all examined in this essay. As a result, the Parthivapuram Temple goes beyond its religious purposes and becomes a catalyst for the social structure of the area to change.